PENGUATAN RANTAI PASOK UMKM MELALUI MANAJEMEN PERSEDIAAN DAN DISTRIBUSI YANG EFISIEN - Bahdin Nur Tanjung; Melisa Nur Asima Sidabutar; Dewi Sartika Situmorang (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This Community Service Program (PKM) program aims to improve the competitiveness of micro-enterprises by strengthening innovation management capabilities in three key areas: product, pricing, and distribution. Partners' common challenges include under-differentiated products, inconsistent quality and packaging, pricing that is not yet cost-based (COGS) and value-based, and distribution that is still limited to local channels. The program is implemented through baseline assessments, practice-based training (workshops), business clinics, innovation trials (rapid testing), and mentoring for the implementation of a 30–60-day action plan. Outputs include a product innovation portfolio (variants/packaging/quality standards), COGS and pricing strategy worksheets, distribution channel maps and order fulfillment SOPs, and a simple KPI dashboard. Targeted outcomes are increased sales, improved margins, expanded distribution channels, and enhanced customer satisfaction.